Conceptual design and functional verification of a novel torque vectoring drive-axle for electric vehicles - Gao, Shoulin; Ge, Qingfa; Shi, Liwei; Xiao, Dong; Hu, Jianlong; Yang, Zewen (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
The conventional power transmission system of electric vehicles typically distributes driving torque equally between the left and right wheels, which restricts the potential to enhance the vehicle’s chassis dynamic performance. To solve this problem, a novel torque vectoring drive-axle (TVDa) is proposed, it can achieve the driving torque precise distribution between the two-side wheels, thereby effectively improving the vehicle's active safety and handling stability. First, the structure design principle and torque distribution mechanism of the novel TVDa is theoretically analyzed in this paper, and establishes the design criteria for key structural parameters. Second, the motor parameters of the TVDa are systematically matched to meet the practical application requirements of the vehicle. Next, a virtual prototype model of an electric vehicle equipped with the TVDa is built, and the functional feasibility of the TVDa impact on vehicle dynamic performance has been verified. Finally, simulation results demonstrate that the novel TVDa can significantly improves the vehicle’s maneuverability and trafficability through distributing driving torque between the two-side wheels, while maintaining low energy consumption in the torque vectoring motor, indicating strong potential for engineering applications.